Uncommon valor [videorecording (DVD)] - Kotcheff, Ted, 1931-; Hackman, Gene; Stack, Robert, 1919-2003; Ward, Fred, 1942- (Paramount, 2017)
A man tries to find his son, who is listed as "missing in action" in Laos, with the help of five of his son's Marine buddies.